Effectiveness in L2 Vocabulary Study – A Classroom-based Investigation of Deliberate Learning - Pauwels, Paul (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
Deliberate vocabulary study has mostly been studied within a strictly experimental framework of learning and memorization. More ecologically valid investigations embedded in existing study contexts have been rare. This study fits into the latter paradigm, investigating how students attempted to learn 90 English words over a period of three weeks and tracking their efforts via study logs and intermediate receptive and productive tests, with final testing five weeks after the study period. The results are in line with findings from earlier research. Study logs showed students mainly relied on different kinds of repetition and retrieval. Selective attention for specific items was an important predictor for short-term learning, and sufficient spacing was the most important predictor for longer-term learning. From a pedagogical point of view, a point of attention is that students mostly practised retrieval after first repeating, making retrieval less difficult and creating an impression of knowledge.